On some modern Ostracoda (Crustacea) from the Tibetan Plateau in SW China, with descriptions of three new species - Peng, Ping; Zhai, Dayou; Smith, Robin J.; Wang, Qianwei; Guo, Yun; Zhu, Liping (Zootaxa, 2021)
Studies of Holocene ostracods of the Tibetan Plateau have mostly centred around valves and carapaces collected from lake sediments, some at or near the substrate surface and others from short cores. Reports from habitats other than lakes are scarce, and few living species found in this region have appendages described, hindering further taxonomic and phylogenetic work. For this study collections of living ostracods were made in mostly ponds, as well as two rivers and one lake. Six species, including three previously undescribed, were recovered: Tonnacypris estonica (Järvekülg, 1960), Arctocypris edita n. sp., Cypris pubera O.F. Müller, 1776, Potamocypris variegata (Brady & Norman, 1889), Ilyocypris tibeta n. sp., and Fabaeformiscandona monticulus n. sp. Specimens of Tonnacypris estonica include males, previously unknown for this species, and suggesting it is a geographical parthenogen. A revision of the fifth limb morphology of the genus Arctocypris, and a subsequent amended diagnosis of the genus are given. Based on carapace and appendage features, Eucypris mareotica (Fischer, 1855) is transferred to this genus: Arctocypris mareotica (Fischer, 1855) com. nov. There are now ca. 100 ostracod species reported from modern or subsurface sediments on the Tibetan Plateau, but only 19 of those can be confirmed as alive when collected (i.e. had appendages intact). The families Limnocytheridae and Ilyocyprididae are both relatively diverse on the plateau compared with the Palaearctic zoogeographical region generally. About one third of ostracod species reported from the Tibetan Plateau are only known from there, suggesting a potentially very high rate of endemism.